Impact of Liquidity, Leverage, and Operating Cash Flow on Financial Distress with Firm Size Moderation - Nabila Sukma Dewi; Mayang Sari Edastami (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This research is to determine the function of company size as a moderating variable in transportation companies listed on the Indonesia Stock Exchange from 2019 to 2023, as well as the influence of liquidity, leverage and operating cash flow on financial distress. Secondary data in the form of annual financial reports of transportation companies listed on the IDX was used in this research. Structural Equation Modeling is analysis technique used, while SmartPLS is used as a bootstrapping method to examine the correlations between the model's variables. The findings show that leverage has a major impact on business size, with a higher level of leverage leading to a smaller firm. Financial distress is significantly influenced by operating cash flow as well; a positive correlation indicates that businesses are under financial strain. In the suggested model, financial distress is not directly influenced by business size, liquidity, leverage, or operating cash flow, as these relationships do not demonstrate substantial effects. Liquidity and operating cash flow also have little influence on business size, suggesting that these factors are not the main factors influencing firm size in the sample.